Risk Profile of High-grade Cervical Lesions and Cervical Cancer Considering the Combination of Cytology, HPV Genotype, and Age among Women Undergoing Colposcopy - Possati-Resende, Júlio César; Fritsch, Thais Zilles; Souza, Karen Cristina Borba (Revista Brasileira de Ginecologia e Obstetrícia / RBGO Gynecology and Obstetrics, 2023)
Objective The present study aims to establish a risk profile for high-grade cervical lesions and cervical cancer (CIN2 + ) in women undergoing colposcopy at the Hospital do Câncer de Barretos, through the analysis of Human Papillomavirus (HPV) infection, cervical cytology, and patient's age.Methods Retrospective cross-sectional study based on a computerized database of women aged ≥ 18 years old who underwent colposcopy at the Prevention Department of the Hospital do Câncer de Barretos from 2017 to 2019.Results A total of 3,411 women were included, 58.0% were positive for high-risk-HPV test, with a higher prevalence of CIN2+ for HPV16 (30.3%) and other HPV (45.0%). Cytological findings that suggest invasive cervical cancer (squamous cells or adenocarcinoma), regardless of the status of HPV test, showed 100% diagnosis of CIN2 + , while atypias that suggest high-grade lesions, HSIL and ASC-H, positive for HPV test, showed in 86 and 55.2%, respectively, diagnosis of CIN2 + . ASC-H cytological results among women aged > 40 years old and negative HPV were mainly associated with benign findings. We observed that ≤ CIN1 has a higher prevalence among older women with negative HPV, while for high-grade lesions there is an increase among young women HPV16- and/or 18-positive. In cancer diagnosis, we observed a predominance of HPV 16/18 regardless of the age group.Conclusion The highest risks of precursor lesions and cervical cancer were found among women with positive HPV 16/18 tests and severe cytological atypia in population screening tests. In addition, cytological findings of ASC-H HPV negative in women > 40 years old usually represent benign findings in histological investigation.
Keywords: squamous intraepithelial lesions of the cervix; uterine cervical neoplasms; papillomavirus infections; colposcopy; risk